Thyrotoxic periodic paralysis: A case report - Ahmad H Asdie Ahmad H Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1987)
The paper presented two cases of periodic paralysis complicating Graves' disease of the Indonesians. Clinical presentation and laboratory findings were concomitant with classical description of thyrotoxic paralysis in these cases. The precipitating factor in our cases is thought to be severe physic- al activities done several hours before paralytic attacks. Hypokalemi a probably also precipitates the episode of paralytic attack, but not convincing since without specific treatment of hypokalemia the paralysis recovered spontaneously. In one case, the periodic paralysis reappeared several time after treatment with anti-thyroid medication, but can be controlled with beta-blockers, propranolol 4 dd 20 mg. Key Words.. thyrotoxic periodic paralysis - Graves' disease - beta-blockers - hypokalemia - Indonesians.